The role of the Dental Surgeon in the prevention of ventilator-associated pneumonia (Research, Society and Development, 2022)
Ventilator-associated pneumonia is at risk of developing with the use of mechanical ventilation, which extends the patient's hospital stay by approximately 5-9 days, in addition to increasing hospital costs. Regarding the etiopathogenesis of VAP, it is known that it occurs through the airways that are contaminated by oral pathogens, by inhalation or aspiration of saliva that is contaminated by bacterial enzymes and oral bacteria. The aim of the present study was to explain the importance of the dentist in the prevention of ventilator-associated pneumonia in the hospital environment and the clinical procedures used. The study was carried out through a literature review, through searches on PubMed, Scielo and Google Scholar, between the years 2017 to 2022, contributing to the construction of this review. In the research carried out in the databases, the descriptors were used, among which 681 articles were found, among them 575 in Google Scholar, 105 in PubMed and 1 in Scielo, finally, only 20 articles were included in the literature review. Thus, it has been proposed that the presence of a dentist, related to the use of chlorhexidine, can reduce the incidence of VAP. Therefore, the dentist is increasingly necessary in the hospital environment with the multidisciplinary team, especially in ICUs due to their important role in the treatment and maintenance of health in hospitalized patients.